Training parents of children with autism spectrum disorder during the diagnosis phase: scoping review protocol - Lemos, Maria (2024)
Introduction: The diagnosis of autism spectrum disorder in children is a complex and demanding process for many families. The support and training provided at the time of diagnosis have a significant impact on the family's experience. Objectives: To map the scientific evidence on strategies for training parents of children with autism spectrum disorder in the diagnostic phase. Methods: Scoping Review protocol based on the Joanna Briggs Institute® methodology. Research conducted in the databases MEDLINE Complete, CINAHL Complete, Cochrane Central Register of Controlled Trials, Nursing & Allied Health Collection: Comprehensive, Cochrane Database of Systematic Reviews Library, Information Science & Technology Abstracts, Open Access Scientific Repositories of Portugal, and Virtual Health Library, with no time limit. Research protocol registered in the Open Science Framework (https://doi.org/10.17605/OSF.IO/HVUA8). Results: The aim is to map strategies for training parents of children with autism spectrum disorder during the diagnostic phase. Conclusion: The protocol outlines the methodology for a Scoping Review that will analyze and synthesize knowledge about strategies for training parents during the diagnosis of children with autism spectrum disorder.